Dynamic strategy adjustment and efficiency enhancement of e-commerce marketing management based on big data analysis - Tan, Maotao; Zhu, Bin (Edelweiss Applied Science and Technology, 2025)
In the current wave of the rapid development of big data technology, the e-commerce industry is undergoing an unprecedented and profound transformation. This study focuses on the optimization and upgrading of e-commerce marketing management strategies in the context of big data. By deeply analyzing the internal influence mechanism of big data on e-commerce marketing and applying empirical research methods, it accurately reveals the inherent connections between key influencing factors and marketing performance, and accordingly proposes highly targeted strategic optimization plans. The research findings indicate that big data plays an irreplaceable and crucial role in core aspects such as precise customer positioning, personalized marketing customization, and scientific evaluation of marketing effectiveness. It can significantly enhance the overall performance of e-commerce marketing. To better adapt to the development trends of the big data era, enterprises should focus on strengthening their data integration and in-depth analysis capabilities, constructing an accurate and efficient marketing system, and further optimizing their customer relationship management strategies, so as to effectively improve their market competitiveness [1]. This study not only provides a solid theoretical foundation for e-commerce enterprises to formulate scientific, reasonable, and practical marketing management strategies but also offers valuable practical guidance for their actual operations, enabling these enterprises to stand out in the fierce market competition.